Steganography Text Message Using LSB and DCT Methods - Bayu Angga Wijaya; Adrian Julio Manalu; Bayu Andreas Tarigan; Lovely Septian Silitonga (Institute of Computer Science (IOCS), 2021)
Advances in human thinking patterns make people realize that information technology is an important part of civilization. In line with the development of information technology, many parties are not responsible for committing crimes such as theft and falsification of information from data. These problems can be overcome using a variety of methods and techniques, one of which is steganography. Steganography is a technique of hiding confidential data in a digital (media) container so that the existence of the secret data is difficult to know by irresponsible people or parties. The purpose of this study is to provide a solution to the problem of hiding messages into images using two different steganographic methods, namely LSB and DCT, then both methods will be tested for their efficiency. In this study, it was concluded that the PSNR value for LSB steganography was 8.887, and the MSE value was 104.85. On the other hand, DCT Steganography got a PSNR of 83,728, and an MSE value of 0.0592. From the PSNR and MSE test results, it can be concluded that the better image quality comes from DCT Steganography, this is because, in processing DCT images, the author must convert the images first, then can encode, but this conversion is not done on the LSB method.